A new synonym for Enicospilus grammospilus (Enderlein, 1921) (Hymenoptera: Ichneumonidae: Ophioninae) - Shimizu, So (Zootaxa, 2018)
The megadiverse genus Enicospilus Stephens, 1835 (Hymenoptera: Ichneumonidae: Ophioninae) comprises over 700 valid species worldwide (e.g. Gauld & Mitchell, 1981; Broad & Shaw, 2016; Shimizu, 2017). Species of this genus are koinobiont endoparasitoids of moderately large sized lepidopteran larva (e.g. Gauld, 1985b; Broad & Shaw, 2016). Members of this genus usually have “ophionoid facies”, characterized by an orange-brown body, extremely large ocelli, long antennae, etc. (Gauld & Huddleston, 1976). Ophionoid facies wasps including Enicospilus are attracted to light and considered to be crepuscular or nocturnal (e.g. Short et al., 2006; Shimizu & Maeto, 2016; Shimizu & Lima, 2018). These wasps usually exhibit a very limited number of diagnostic characters and as a consequence the delimitation and recognition of species is very difficult, and causes many taxonomic confusions including synonyms, homonyms and misidentifications.